KEUNGGULAN KOMPETITIF GULA CAIR KIMPUL - Rejeki, Fungki Sri; Puspitasari, Diana; Wedowati, Endang Retno (Journal of Research and Technology, 2017)
The need for sugar as a sweetener is increasing, therefore need to look for alternative other sweeteners as sugar cane substitution, among them by developing liquid sugar from starch. Purse as one type of root crops have a great opportunity to be developed because it has a high carbohydrate content. The purpose of this research was to determine the best process of purse liquid sugar with acid hydrolysis and enzyme hydrolysis. This research consists of 2 stages. The first stage is the processing optimization by acid hydrolysis and the second stage is the processing optimization by enzyme hydrolysis. The parameters tested were oBrix, moisture content, ash content, and reducing sugar. The best process is based on the highest expectation value based Value Expectations Method. Furthermore, the products produce from the selected process calculated caloric value and the Glycemic Index (GI). The results of this research showed that: (1) The best acid hydrolysis process is adding acid 15 ml  and hydrolysis time are 1 hour, which produces purse liquid sugar with 86.30% moisture content, 2,01% ash content, 13,33oBrix, 10,21% reducing sugar, 41 calories and IG value is 47,32; (2) The best enzyme hydrolysis process is adding 3 ml enzyme and hydrolysis temperature of 1000C, which produces purse liquid sugar with 73.73% moisture content, 0.24% ash content, 25.17 oBrix, 23,43% reducing sugar, 106 calories and IG value is 80.63.